The use of our gastro-cultural heritage in tourism - Minorics Tünde; Gonda Tibor (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola-V. Pagyak Kiadója, 2014)
Abstract. In recent years tourism industry has been experiencing a growing demand for products standing for local uniqueness and values. In the given study an attempt has been made at outlining possibilities of utilization of local products with regard to tourism. The uniqueness and value of our gastronomic and cultural heritage may help to bring forth a new attractive service structure in the tourism business. In the thesis nutrition related habits have been presented, and what heritage, local identity, interrelation between tradition and modernity in the field of gastronomy mean for modern people.

Az utóbbi évek egyre erősödő trendje, hogy a turizmus kínálatában is keresik az egyediséget és a helyi értékeket hordozó termékeket. A szerzők írásukkal a helyi termékek turisztikai hasznosításának a lehetőségére szeretnék ráirányítani a figyelmet. A gasztrokulturális érétkeink éppen az örökségi értékeikkel és egyediségükkel segíthetik a turizmus ágazat új, vonzó kínálati struktúrájának a kialakítását. Az értekezésben bemutatják a táplálkozáshoz kapcsolódó szokásokat, és azt, hogy a ma élő ember számára mit is jelent az örökség, a helyi identitás, a hagyomány és a modernitás egymáshoz való viszonya a gasztronómia területén.
Gasztrokulturális örökségünk turisztikai hasznosítása
http://www.kmf.uz.ua/hun114/letoltes/limes/LIMES2014.pdf
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00000415
Keywords: gastronomy; culture; heritage; region; nutrition; habits; ethnicities; local identity